Ansible for VMware by examples : a step-by-step guide to automating your VMware infrastructure - Berton, Luca (Apress, 2023)
Learn to use the Ansible open source IT automation tool to automate your VMware infrastructure. This book contains all of the obvious and not-so-obvious best practices of Ansible automation. Each lesson summarizes a specific use case for the modern VMware infrastructure and is focused on a single module from the most important parameter, including live demo of code and real-life usage. You'll configure the Ansible Controller to interact with VMware infrastructure using the "community.VMware" Ansible documentation collection and the appropriate Python libraries. Next, learn how to automate the creation of a virtual machine manually and from a template, start and stop using the shutdown and forced-power off a Virtual Machine, take and delete and snapshot, add a new hard disk and expand a currently attached hard disk, as well as gather information for data centers, clusters, host systems, and virtual machines. By the end of this book, you'll be well-versed in efficiently maintaining a VMware infrastructure with Ansible Automation. You'll also be able to save time and reduce manual errors using simple human-readable automation technology.